Effects of Initial Moisture Content on Boil Bending Properties of Solid Rubberwood (Hevea Brasiliensis) - Choo, Koh Boon (2001)
In recent years, there has been a high demand for rubberwood in the wood based industry in Malaysia, and this demand is expected to increase further. Inefficient use of resources not only leads to higher production cost but also increases the demand for industrial wood supply. Currently, most of the furniture makers in Malaysia are trying to cut down their production cost in order to maintain a competitive edge. One way to reduce production cost is to use the technique of steam or boil bending of solid rubberwood. This can increase the wood utilization efficiency by 30%, simplify of production process and enable greater process automation. This study was carried out to investigate the effects of initial moisture content on boil bending properties of rubberwood, specifically comparing the percentage and type of defects. Initial wood moisture contents of below 10% and 20-25% were used to investigate the boil bending properties of rubberwood. The recovery rate of boil bending of solid rubberwood was found to improve by about 6% when the initial wood moisture content was increased from 10% to 20-25%. In order to minimize the production cost, it is recommended to use initial wood moisture content of 20-25% instead of the current practice of below 10%.